Turn-Around Strategy to Develop Community-Based Ecotourism on The Maratua Island, Indonesia - Yudha Wahyu Pratama; Samodra Wibawa; Abdul basith Ramadhan; Rizki Rahmasari (Journal of Public Administration and Local Governance, 2022)
This paper aims to find out the most appropriate strategy to develop community-based ecotourism on the Island of Maratua, East Kalimantan, Indonesia. This paper employs a descriptive research method with qualitative analysis techniques. Data was collected through observations, interviews, Focus Group Discussions (FGDs), and documentation studies. The data were further analyzed using the SWOT Analysis, which compares internal factor analysis system (IFAS) and external factor analysis system (EFAS). The results show that Maratua is in Quadrant III in the SWOT diagram. It means that community-based ecotourism on Maratua has an opportunity to develop despite internal weaknesses. It is suggested that in the future Maratua should be developed through a turn-around strategy, i.e., weakness–opportunity (WO) strategy, a redesign of the island, a strengthening of community capacity, a make-up of supporting facilities, and an improvement of social institutions.